2004
DOI: 10.1016/j.cub.2004.11.051
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Fragmentation after Induction of a Double-Strand Break Is an Active Process Prevented by the RMX Repair Complex

Abstract: Chromosome aberrations are common outcomes of exposure to DNA-damaging agents or altered replication events and are associated with various diseases and a variety of carcinomas, including leukemias, lymphomas, sarcomas, and epithelial tumors. The incidence of aberrations can be greatly increased as a result of defects in DNA repair pathways. Although there is considerable information about the molecular events associated with the induction and repair of a double-strand break (DSB), little is known about the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
135
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(152 citation statements)
references
References 19 publications
15
135
2
Order By: Relevance
“…7C) such as the MRX complex or the Rad52 protein (Kaye et al 2004;Lobachev et al 2004). Inability to maintain end coordination when the donors are physically separated could then result in loss of signaling between the ends, causing a shift from the quick and efficient GC mode of repair to the slow and inefficient BIR mode of repair (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…7C) such as the MRX complex or the Rad52 protein (Kaye et al 2004;Lobachev et al 2004). Inability to maintain end coordination when the donors are physically separated could then result in loss of signaling between the ends, causing a shift from the quick and efficient GC mode of repair to the slow and inefficient BIR mode of repair (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mre11 has 39 to 59 exonuclease activity and both Mre11 and Sae2 have endonuclease activity (Bressan et al 1998;Lee et al 2002;Nicolette et al 2010); however, mutation of the nuclease activity of Mre11 has very little effect on resection (Bressan et al 1998;Moreau et al 1999;Lee et al 2002). Mre11's nuclease activity is required in mitotic cells to cleave hairpin ends (Lobachev et al 2004;Yu et al 2004) and in meiosis to remove the Spo11 protein from DSB ends (but in both of these cases Sae2 is also necessary). Deleting Sae2 does significantly retard resection (Clerici et al 2005).…”
Section: For Details)mentioning
confidence: 99%
“…The interaction between DatmA and bimE could reveal a relationship between DSBs and the mitotic spindle checkpoint. Lobachev et al (2004) have shown that the Mre11 complex is required in vivo to hold the two ends of a broken chromosome together throughout DSB repair. The same authors have shown that a mutation in the Rad50 Zn-hook structure resulted in DNA ends that are dispersed in 10-20% of cells.…”
Section: Chk2mentioning
confidence: 99%
“…The same authors have shown that a mutation in the Rad50 Zn-hook structure resulted in DNA ends that are dispersed in 10-20% of cells. The Mre11 complex holds broken ends together and counteracts mitotic spindle forces that can be destructive to damaged chromosomes (Lobachev et al 2004). Malavazi et al (2005) have shown epistatic and synergistic interactions between sldI RAD50 and bimE APC1 at S-phase checkpoints and in response to HU and UV light.…”
Section: Chk2mentioning
confidence: 99%